On the body promoting function and value of Taijiquan to different crowd from the angle of Human Body Science - Qin, Shaobing; Zhang, Xiao (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: From the perspective of Human Body Science, this paper probes into the body promotion function of Taijiquan in different groups, so as to let the public understand the value of Taijiquan, and thus attract more people to love and participate in Taijiquan, to further promote and enhance the level of public health. Methods: PubMed database, China Hownet, Cochrane Library Database, China Biomedical Literature Database and Wanfang Journal articles were searched by literature method, to collect the Randomized controlled trial and clinical control test of Taijiquan’s influence on human body. By using the method of logical analysis, this paper analyzes the body promoting function and value of Taijiquan in different people, and then expounds the human body scientific value of Taijiquan, so as to deepen the public’s understanding, attention and love of Taijiquan, to promote better combination and development of Taijiquan and public health. Results: (1) long-term Taijiquan exercise in the normal population, the body can improve the content of serum inflammatory factors, intestinal Bifidobacterium, and also has a benign effect on the regulation of depression. Taijiquan exercise can also improve the knee function of the human body to improve the effect of muscle strength, body composition, improve the range of motion of human joints and body balance. (2) long-term Taijiquan exercise can improve the physical fitness, cardiopulmonary fitness, flexibility and so on. And the body fat rate of teenagers can play a role in reducing the role of body fat, on the adolescent bad mood can be vented. The long-term exercise of Taijiquan can improve and promote the function of the body, relieve the tension and pressure of the mind, improve the quality of sleep and promote the healthy development of the mind. Taijiquan also has health promoting effects on the cardiovascular system and respiratory system development in adolescents. Practicing Taijiquan can also relax the muscles of the waist, back, shoulder and neck of teenagers, which can help to relieve the pain caused by sitting for a long time. (3) long-term Taijiquan exercise in the middle-aged and elderly groups can play a health promotion role on the transcutaneous partial pressure of oxygen in the knee joint and the skin microvasculature. Through Taijiquan, it can improve the heart, lung function and sports ability of the middle-aged and old people, promote the improvement of cognitive function and balance ability, enhance their balance ability and body immunity, flexibility and muscle strength, in order to reduce the incidence of diseases in the elderly population. Taijiquan exercise can also improve the body bone density of the middle-aged and elderly people, alleviate the osteoporosis caused by aging and other problems, and reduce blood lipids and blood sugar in the middle-aged and elderly people, improve sleep quality and gastrointestinal function, it also has a good effect in improving anxiety and depression. (4) in the group of patients, Taijiquan exercise in different groups of patients with different conditions for their health promotion role. In patients with chronic pain, long-term Taijiquan exercise can make their pain to a certain degree of relief. In patients with mild hypertension, long-term Taijiquan exercise can promote the effect of sympathetic and parasympathetic nervous system regulation on the body, improve the immune function, improve the mechanism of neural regulation, and thereby control the fluctuation of blood pressure, to lower its systolic pressure. In patients with obstructive pulmonary disease, Taijiquan can reduce their inflammatory factors, reduce their condition, improve their mood, improve mental health. In the arthritis patient community, Taijiquan exercise can improve the patient’s movement ability, reduces the arthritis patient’s symptom. In the group of patients with diabetes, Tai Chi exercise can improve their cardiopulmonary endurance, play a role in reducing their fasting blood glucose and promote rehabilitation. In patients with functional ankle instability, Taijiquan exercise can improve their ability to balance the body, reduce the disease. In the Group of patients after breast cancer operation, long-term Taijiquan exercise can promote the circulation of body fluid, increase physical activity, maintain the normal operation of the body and cell reproduction, reduce the recurrence rate of breast cancer. In the Group of patients with mild cognitive impairment, long-term Tai Chi exercise can improve their memory. In patients with heart disease, Tai Chi exercise can play a role in promoting their recovery process. (5) from the relationship between exercise intensity and exercise effect of Taijiquan, the duration of each exercise is from 30 minutes to 60 minutes, the frequency is about 5 times a week, and the interval of each exercise is less than 2 days, this kind of exercise pattern and exercise intensity can achieve the good exercise effect. Conclusion: (1) the future research on Taijiquan will focus on more different characteristics and age groups. (2) Taijiquan has a good effect and high value on the promotion of human health. It is suitable for many groups and people of all ages as a way of physical exercise. (3) to propagandize the value and function of Taijiquan to the masses, which is helpful to enhance the masses’understanding, value and love of Taijiquan. (4) starting from national fitness, to popularize Taijiquan in an all-round way will be conducive to the combined development and mutual promotion of national fitness and Taijiquan, and will play an important role in promoting and guiding the construction of a healthy China, is Conducive to the improvement of the health level of the whole people.